The impact of videogames on the mood of amateur youth players during consecutive games - Mateo-Orcajada, Adrián; Vaquero-Cristóbal, Raquel; Gallardo-Guerrero, Ana María; Abenza-Cano, Lucía (Frontiers in Sports and Active Living, 2023)
Introduction Esports have experienced tremendous growth in recent years. In the scientific field, previous research has shown the determining role of psychology in competitive performance, but little is known about the factors that may be more determinant. In addition, in the amateur field, where fun and enjoyment are the most important factors, it has been observed that players can see their psychological state altered due to different factors, but it is not known if the outcome of the game (win or lose) can be influential. For this reason, the aim of the present investigation was to analyze changes in players' mood between three consecutive games as a function of the outcome of each game. Methods A total of 14 amateur players participated in the research, all of them with previous experience and being regular League of Legends players. The participants completed the POMS questionnaire before the start of each game and the outcome of each game was recorded at the end. Results The results showed that no significant pre-game differences were found in any of the games, regardless of winning or losing. Significant differences were found in the pre-game mood between the first and second game, according to the outcome of the first game, and between the second and third game, according to the outcome of the second game. Between the first and second games, there was a significant increase in depression (p = 0.038) and anger (p = 0.003) when the first game was lost; and between the second and third games, there was a decrease in tension (p = 0.003) and anger (p = 0.022) when the second game was won. In addition, it should be noted that fatigue increased significantly after each game, regardless of the outcome, and with respect to the change in mood, this was more noticeable when the first game was lost and the second was won, as significant changes were observed in tension (p = 0.028), depression (p = 0.030) and anger (p = 0.006). Conclusion Pre-match mood does not influence post-match performance, but mood changes do occur between successive matches depending on the outcome of the match.